INVESTIGATING EFL LEARNERS’ INQUIRY PROCESS IN ACADEMIC READING - Hendi hidayat; sumadi sumadi (IAIN Syekh Nurjati Cirebon, 2019)
For a higher-order comprehension, academic reading class at IAIN Syekh Nurjati Cirebon is designed to develop the EFL learners’ critical reading, and to draw their awareness to the relationship between reading and writing. The study was intended to find out how the students are engaged critically to respond to academic texts, and express an informed opinion on issues addressed in a written form. The idea of reading response is influenced by the work of Rosenblatt. For her, reading transaction is an active event. Although this theory was widely applied in literature major, but the writer sees such a valuable thing to bring this theory into academic reading setting. Qualitative data are presented, which demonstrate how critically minded these learners are when engaging with texts. The author gathered data for this analysis by conducting observation, interview and document analysis of learners’ written work.This article concludes with suggestions for how teachers can develop their own critical literacy approach to texts and units. The research concludes that the EFL learners presented in this study established a careful selection of texts, activation of their background knowledge, questions to the author’s ideas, intertextuality for answering the questions, and reflection in finishing their product.